Masked uncontrolled hypertension in patients with impaired carbohydrate metabolism - V. V. Nazarova; O. N. Antropova; I. V. Osipova; A. N. Zhuravleva; M. I. Semenova (Российский кардиологический журнал)
Aim. To establish the prevalence of masked uncontrolled hypertension (HTN) (MUH) in patients with diabetes or impaired glucose tolerance (IGT) and determine its clinical and hemodynamic characteristics.Material and methods. The study involved 87 patients who received regular antihypertensive therapy for hypertension and had established diabetes or IGT. The mean age of patients was 62,6±9,9 years, of which 51,7% were women, 48,3% — men. Type 2 diabetes was revealed in 77,7%, IGT — 22,8% of patients. For 24-hour blood pressure monitoring, BpLAB system (OOO Petr Telegin) was used; blood pressure (BP) was determined in the brachial artery, central blood pressure — in the aorta. We analyzed risk factors and target organ damage. The results were processed using the Excel Microsoft Office 2007 package and the Statistica 6.0 and 10.0 package from StatSoft, Inc (USA).Results. Uncontrolled hypertension was revealed in 59,8%, MUH — in 18,4%, controlled HTN — 21,8% of patients. Mean daytime and mean nighttime systolic BP in patients with MUH and uncontrolled HTN were comparable. Patients with controlled hypertension compared with MUH had lower mean day- and nighttime aortic BP by 27,1% (p<0,01) and 16,8% (p<0,01), respectively. Aortic BP was comparable in individuals with MUH and uncontrolled HTN. Asymptomatic hyperuricemia was more common in patients with uncontrolled HTN compared with MUH and controlled hypertension by 29,3% and 41,8%, respectively. With MUH, compared with controlled HTN, we revealed a higher incidence of stroke by 18,8%, a decrease in glomerular filtration rate <60 ml/min by 17,5%, albuminuria by 18,8%, left ventricular hypertrophy by 2,6 times.Conclusion. Only 41,2% of patients with diabetes and prediabetes achieve the target office BP level, while every second of these patients has MUH. MUH, compared with controlled HTN, is characterized by a higher incidence of stroke, kidney (decrease in glomerular filtration rate <60 ml/min and albuminuria) and heart damage (left ventricular hypertrophy).